Mohamed Fakir (Dairy Farmer) - Raipur Gujra, Punjab India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Mohamed Fakir is a a dairy farmer in Punjab India. He describes in the video how his cows milk production is steadily decreasing, largely due to the the changing climate and to the lack of water and water infrastructure. Mohamed is also concerned with the reduction in farmers choosing to produce fodder. Farmers nowadays grow cash crops he explains, and thus it is getting increasingly difficult to get enough fodder for the animals..